Voluntary disclosure of corporate venture capital investments - Mohamed, Abdulkadir; Schwienbacher, Armin (Journal of Banking & Finance, 2016)
In this paper, we investigate drivers of corporate venture capital investment announcements. Consistent with voluntary information disclosure theories, we find that a public announcement is less likely to be made when the start-up firm is in the seed stage but more likely when the parent company is large, active in concentrated markets and in non-high-tech industries; spends heavily on internal R&D and capital expenditures; has low leverage ratio; and faces more information asymmetry problems. In addition, corporate venture capital programs managed externally disclose more often than internal programs. We find that parent companies facing more severe asymmetric information problems enjoy the highest abnormal returns in response to announcements. This study contributes to the literature on voluntary information disclosure in that it evidences that larger corporations use disclosure of some of their investments in innovative startups strategically as a way to convey valuable information to the market.